Lifelong arrhythmic risk stratification in arrhythmogenic right ventricular cardiomyopathy: distribution of events and impact of periodical reassessment. Issue Volume 20:Issue FI 1(2018) (13th June 2017) - Cappelletto, Chiara; Stolfo, Davide; De Luca, Antonio; Pinamonti, Bruno; Barbati, Giulia; Pivetta, Alberto; Gobbo, Marco; Brun, Francesca; Merlo, Marco; Sinagra, Gianfranco
Abstract: Aims: The arrhythmic risk stratification of arrhythmogenic right ventricular cardiomyopathy (ARVC) remains controversial. We evaluated the long-term distribution of life-threatening arrhythmic events assessing the impact of periodical risk reassessment. Methods and results: Ninety-eight ARVC patients with no previous major ventricular arrhythmias were retrospectively analysed. Patients were assessed at baseline, at 22 [inter-quartile range (IQR) 16–26], 49 (IQR 41–55) and 97 months (IQR 90–108). The primary endpoint was a composite of sudden cardiac death, ventricular fibrillation, sustained ventricular tachycardia or appropriate implanted cardioverter-defibrillator intervention. During a median follow-up of 91 months (IQR 34–222) 28 patients (29%) experienced the composite endpoint. The median time for the primary event was 35 months (IQR 18–86 months), and 39% of events occurred beyond 49 months of follow-up. History of syncope (HR 4.034; 95% CI, 1.488 to 10.932; P -value = 0.006), non-sustained ventricular tachycardia (NSVT; HR 3.534; 95% CI 1.265–9.877; P -value = 0.016), premature ventricular contractions (PVC) >1000/24h (HR 2.761; 95% CI 1.120–6.807; P -value = 0.027), and right ventricular fractional area change (RVFAC; HR 0.945; 95% CI 0.906–0.985; P -value = 0.008) were found as independent predictors at baseline multivariate analysis. Nevertheless, when the prognostic impact of each variable was reassessed overtime only NSVT (HR 3.282; 95% CI, 1.122 to 9.598, P -value = 0.023) and RVFAC (HR 0.351, 95% CI, 0.157 to 0.780; P -value = 0.010) remained independent predictors throughout the whole follow-up. Conclusion: In our cohort of ARVC patients only NSVT and RVFAC maintained their independent prognostic impact in predicting arrhythmic events during the long-term follow-up. Periodical re-assessment of risk in these patients is strongly recommended.